A multicentre study comparing post-mortem SARS-CoV-2 antibody testing in Cape Town mortuaries - Tayna Carlisle; Yuvika Vandayar; Laura Taylor; Itumeleng Molefe; Lorna J. Martin; Candice Wilscott-David; Janette Verster; Christoffel Opperman; Laura J. Heathfield (Southern African Journal of Infectious Diseases)
Background: Coronavirus disease 2019 (COVID-19) was recognised as a global pandemic in 2019, yet the exact number of infections is still unclear. In addition, there is limited research on post-mortem antibody testing.